Bystander dispatcher-assisted cardiopulmonary resuscitation for the likelihood of an initial shockable rhythm after out-of-hospital cardiac arrest. (14th October 2021) - Goto, Y; Funada, A; Maeta, T; Goto, Y
Abstract: Background/Introduction: The association of bystander dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) and no bystander CPR with the likelihood of an initial shockable rhythm at emergency medical services (EMS) arrival or the likelihood of reduced time interval to initiation of CPR after out-of-hospital cardiac arrest (OHCA) is poorly explored. We hypothesised that more patients who received bystander DA-CPR would have an initial shockable rhythm than those without bystander CPR (NO-CPR) and that DA-CPR would reduce the time to initiation of CPR (collapse-to-first CPR time) compared with NO-CPR. Purpose: To study the incidence rate of initial shockable rhythm recorded by EMS personnel and the collapse-to-first CPR time in the DA-CPR and NO-CPR cohorts Methods: Our study included 97, 690 patients (age, ≥18 years), who had an OHCA with a presumed cardiac origin witnessed by a layperson, from a prospectively recorded Japanese nationwide Utstein-style database between 2013 and 2017. The patients were divided into the DA-CPR (n=42, 767) and NO-CPR (n=54, 923) groups. The primary endpoints were initial shockable rhythm recorded by the EMS after arrival and the time from collapse to CPR initiation. The secondary endpoints were 1-month survival and neurologically intact survival. A Cox proportional hazards model was used to compare the incidence rate of initial shockable rhythm before/after propensity score (PS) matching. Results: The crude rate of the initial shockable rhythm in the DA-CPR group was significantly higher than that in the NO-CPR group: before PS matching, 21.7% (9270/42, 767) vs. 17.5% (9605/54, 923); after PS matching, 22.2% (8965/39, 426) vs. 17.1% (6728/39, 426), both p<0.0001. The Cox proportional hazards model showed that DA-CPR was associated with the likelihood of initial shockable rhythm before (adjusted hazard ratio [aHR], 95% confidence interval [CI]: 1.23, 1.21–1.25; p<0.0001) and after PS matching (aHR, CI: 1.05, 1.03–1.06; p<0.0001) compared with NO-CPR. Collapse-to-first CPR time in the DA-CPR group was significantly shorter than that in the NO-CPR group regardless of PS matching: before PS matching, mean 4.2 (SD 6.0) min vs. 11.7 (8.0) min; after PS matching, 4.1 (5.6) min vs. 12.6 (8.6) min, both p<0.0001. One-month survival and neurologically intact survival rates were significantly higher in the DA-CPR group than in the NO-CPR group after PS matching: survival, 11.5% (4520/39, 426) vs. 8.3% (3255/39, 426); neurologically intact survival, 7.5% (2944/39, 426) vs. 4.4% (1719/39, 426), p<0.0001. Conclusions: Patients who received DA-CPR after experiencing OHCA due to presumed cardiac causes were more likely to have an initial shockable rhythm than those who did not receive bystander CPR. Moreover, first CPR was performed approximately 8 min earlier in the DA-CPR group than in the NO-CPR group. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Japan Society for the Promotion of Science (Grant-in-Aid for Scientific Research)